Effects of double-procedure homogenization heat treatment on microstructure and mechanical properties of WE43A alloy. (25th July 2018) - Sun, Qing Ya; Wang, Li Ping; Liu, Dong Rong; Guo, Er Jun
Abstract: In order to improve mechanical properties of WE43A alloy and enhance production rates of castings in plastic deformation process, effects of double-procedure homogenization heat treatment (DHHT) on microstructure and mechanical properties of WE43A alloy were investigated and characterized by optical microscope (OM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), x-ray diffraction (XRD) and tensile tests. Results showed that eutectic Mg41 Nd5 phase at grain boundaries completely dissolved into α -Mg matrix after the single-procedure homogenization heat treatment (SHHT) at 520 °C/8 h. However, eutectic Mg24 Y5 phase with a small amount still existed in microstructure. After DHHT at 510 °C/12 h, eutectic Mg24 Y5 phase completely dissolved into the matrix. After application of DHHT, the yield strength, ultimate tensile strength and elongation reached the maximum. The corresponding values were 110 MPa, 243 MPa and 21%. The morphology of tensile fractures varied from the mixed transgranular-intergranular fracture for the as-cast alloy to the transgranular cleavage fracture for the DHHT-treated alloy.